The COHERENT Methodology in FunGramKB - Periñán-Pascual, Carlos; Mairal-Usón, Ricardo (Onomázein, 2011)
Recent research has been done synergistically between FunGramKB, a lexical-conceptual knowledge base, and the lexical constructional model, a linguistic meaning construction model. since concepts are claimed to play an important role in the design of the cognitive-linguistic interface, this paper discusses the methodology adopted in structuring the basic conceptual level in the FunGramKB core ontology. more particularly, we describe our four-phase coHeRenT methodology (i.e. conceptualization + Hierarchization + Remodelling + refinemenT), which guided the cognitive mapping of the defining vocabulary in longman Dictionary of contemporary english.